Characterization of bismuth selenide (Bi2Se3) thin films obtained by evaporating the hydrothermally synthesised nano-particles. (March 2016) - Indirajith, R.; Rajalakshmi, M.; Gopalakrishnan, R.; Ramamurthi, K.
Abstract: Bismuth selenide (Bi2 Se3 ) was synthesized by hydrothermal method at 200 °C and confirmed by powder X-ray diffraction (XRD) studies. The synthesized material was utilized to deposit bismuth selenide thin films at various substrate temperatures (Room Temperature-RT, 150 °C, 250 °C, 350 °C and 450 °C) by electron beam evaporation technique. XRD study confirmed the polycrystalline nature of the deposited Bi2 Se3 films. Optical transmittance spectra showed that the deposited (at RT) films acquire relatively high average transmittance of 60%in near infrared region (1500–2500 nm). An indirect allowed optical band gap calculated from the absorption edge for the deposited films is ranging from 0.62 to 0.8 eV. Scanning electron and atomic force microscopy analyses reveal the formation of nano-scale sized particles on the surface and that the nature of surface microstructures is influenced by the substrate temperature. Hall measurements showed improved electrical properties, for the films deposited at 350 °C which possess 2.8 times the mobility and 0.9 times the resistivity of the films deposited at RT. Highlights: Bismuth selenide films were synthesised. Optical band gap for the films lies in the range of 0.62–0.8 eV. Hall measurement studies confirm improved electrical properties at 350 °C.